2010
DOI: 10.1002/jso.21813
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic analysis of adenosquamous/squamous cell carcinoma of the gallbladder

Abstract: AS/SCC of the gallbladder is often diagnosed at an advanced stage, which results in non-curative surgical resection and a poorer prognosis than conventional GBC. However, curative surgical resection of AS/SCC of the gallbladder might result in disease-free survival rates that are comparable with those of conventional GBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 14 publications
8
54
1
Order By: Relevance
“…Therefore, the present study attempted to compare patients with these different histopathological subtypes to assess the correlation between their clinicopathological characteristics and the PTMA/PTMS expression in SC/ASC and AC of the gallbladder. In the present study, patients with SCC/ASC of the gallbladder accounted for 4.34% (46/1,060) of the total patients with carcinoma of the gallbladder treated at the participating hospitals, which is consistent with the incidence reported in earlier studies (2,6,20). Similar to the clinical presentation of AC, patients with early-stage SCC and ASC presented with no specific symptoms other than those typically associated with chronic cholecystitis, due to which the majority of patients were not diagnosed at an early stage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, the present study attempted to compare patients with these different histopathological subtypes to assess the correlation between their clinicopathological characteristics and the PTMA/PTMS expression in SC/ASC and AC of the gallbladder. In the present study, patients with SCC/ASC of the gallbladder accounted for 4.34% (46/1,060) of the total patients with carcinoma of the gallbladder treated at the participating hospitals, which is consistent with the incidence reported in earlier studies (2,6,20). Similar to the clinical presentation of AC, patients with early-stage SCC and ASC presented with no specific symptoms other than those typically associated with chronic cholecystitis, due to which the majority of patients were not diagnosed at an early stage.…”
Section: Discussionsupporting
confidence: 92%
“…The population of the present study mainly included patients with advanced stages of SCC, ASC and AC. Several previous studies have described that SCC and ASC of the gallbladder with a squamous cell component exhibit a greater proliferation capability, lower propensity for metastasis, greater tendency for involvement of adjacent organs, and worse overall prognosis, as compared with that associated with AC of the gallbladder (2)(3)(4)(5)(6). In the present study, no significant difference was observed with respect to the incidence of lymph node metastasis, and invasion of the surrounding tissues and organs between the SCC/ASC and AC groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The OCUG-1 cell line represents a poorly differentiated adenocarcinoma and is regarded as a unique cell line because the corresponding cancer is a transitional form from adenocarcinoma to squamous cell carcinoma (22). Generally, GBC is classified into three histological types: adenocarcinoma, which accounts for 90% of all primary gallbladder cancer cases, followed by squamous carcinoma and adenosquamous carcinoma, both of which display an incidence of 1.4-10.4% (23,24). Although the clinical features of squamous carcinoma and adenosquamous carcinoma are similar to adenocarcinoma of the gallbladder, squamous and adenosquamous carcinoma patients frequently presented with an advanced stage of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The major subtype of GBC is adenocarcinoma (AC), which accounts for >90% of GBC cases (1), while squamous cell/adenosquamous carcinoma (SC/ASC) is a rare subtype, comprising 1.4–10.4% of GBC cases (2). Notably, the 5-year survival of patients with GBC involving these two subtypes is extremely low.…”
Section: Introductionmentioning
confidence: 99%